Kritik Arsitektur Dalam Cerpen “Arsitektur Kesunyian” Karya Sungging Raga - Ainun Tenri Milinia Putri; Dea Mustika; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Architectural criticism is not only used on physical buildings but can also be found in literary works, one of which is in the short story entitled Architecture of Silence by Sunggung Raga. The aim of this research is to find architectural criticism contained in short stories using descriptive methods which is a way of solving problems using analyze and read carefully the architectural aspects contained in the short story. Take several short story quotes and explain them into aspects of descriptive criticism, namely static, dynamic and process aspects